Effectiveness of the Make a Match Model Based on Flashcard Media to Improve Students' Learning Outcomes on Fractions - Nisrina Nila Fauzizah; Trimurtini Trimurtini; Ika Ratnaningrum (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
The low results Study mathematics material fractions in elementary school are caused by the abstract nature of the material and patterns, teaching isolated, teacher-centered. This study aims to test effectiveness application of the make-a-match model assisted by flashcard media to improve results Study mathematics material fractions compared with the Problem Based Learning (PBL) model. This type of research is a quantitative experiment with a quasi-experimental design with a non-equivalent control group design. Instrument data collection in the form of test results Study mathematics objective, 26 items, question choice double, which was tested as a pretest and posttest (Cronbach's alpha of 0.703). The data analysis technique uses statistical tests, descriptive and inferential, which include prerequisite tests and hypothesis testing using an independent-samples t-test and paired-samples t-test. The pretest results showed that the initial abilities of the two groups were relatively balanced with an average of 58.16 for the experimental class and 53.80 for the control class. After the intervention, the results showed a significant difference in learning outcomes between the two groups based on the independent samples t-test with a t value of 4.124, df = 58, and a p value < 0.001. The experimental class obtained a posttest average of 83.43, significantly higher than the control class (PBL), which obtained an average of 75.57. In addition, the Normalized Gain (N-Gain) test proved that the experimental class increased by 57.18% (moderate and more effective category), outperforming the control class, which only achieved 45.38% (moderate and quite effective category). Based on these results, it can be concluded that the application of the make-a-match model assisted by flashcard media is more effective in improving the mathematics learning outcomes in fractions compared to the use of the problem-based learning (PBL) model.